(untitled) (Eastern Journal of Medical Sciences, 2019)
Background: Latent Cytomegalovirus (CMV) infections may be reactive in consequence of immunosuppression. Recently, CMV-associated uveitis cases have also been reported in immunocompetent individuals. Aim: The aim of this study was to obtain epidemiological data by evaluating CMV DNA PCR results, clinical characteristics and risk factors of patients diagnosed with viral uveitis. Methods: Between the years 2011-2017, anterior chamber fluid samples of 35 patients with viral uveitis sent from the ophthalmology clinic to the Virology Laboratory were included in this study. CMV DNA real-time PCR results were evaluated. Results: CMV DNA positivity was detected in 9 (26%) of the 35 patients. CMV DNA positivity was highest (13%) in over 60 years (p=0.02). Acute recurrent uveitis in 44% (4/9) of patients, single eye involvement in 78% (7/9) and anterior uveitis in 44% (4/9) were found. Conclusion: In this study, CMV DNA positivity was detected in 26% of the patients with viral uveitis. Considering the presentations of a small number of cases related to CMV uveitis in our country, this study is important due to being the most comprehensive study in our country.